Impaired quality of life, but not cognition, is linked to a history of chronic hypercortisolism in patients with Cushing’s disease in remission - Pupier, Emilie; Santos, Alicia; Etchamendy, Nicole; Lavielle, Aurélie; Ferriere, Amandine; Marighetto, Aline; Resmini, Eugenia; Cota, Daniela; Webb, Susan M.; Tabarin, Antoine (Frontiers in Endocrinology, 2022)
Context. Impaired cognition and altered quality of life (QoL) may persist despite long-term remission of Cushing’s disease (CD). Persistent comorbidities and treatment modalities may account for cognitive impairments. Therefore, the role of hypercortisolism per se on cognitive sequelae remains debatable. Objective. To investigate whether memory and QoL are impaired after long-term remission of CD in patients with no confounding comorbidity. Design and Setting. Cross-sectional case-control study in two tertiary referral centers Patients. 25 patients (44.5 ± 2.4 years) in remission from CD for 102.7 ± 19.3 Mo and 25 well-matched controls, without comorbidity or treatment liable to impair cognition. Main Outcome Measure(s). Hippocampus- and prefrontal cortex-dependent memory, including memory flexibility and working memory, were investigated using multiple tests including sensitive locally-developed computerized tasks. Depression and anxiety were evaluated with the MADRS and HADS questionnaires. QoL was evaluated with the SF-36 and CushingQoL questionnaires. The intensity of CD was assessed using mean urinary free cortisol and a score for clinical symptoms. Results. CD patients displayed similar performance to controls in all cognitive tests. In contrast, despite the absence of depression and a minimal residual clinical Cushing score, patients had worse QoL. Most of the SF36 subscales and the CushingQoL score were negatively associated only with the duration of exposure to hypercortisolism (p≤ 0.01 to 0.001). Conclusions. Persistent comorbidities can be a primary cause of long-lasting cognitive impairment and should be actively treated. Persistently altered QoL may reflect irreversible effects of hypercortisolism, highlighting the need to reduce its duration.